TINJAUAN YURIDIS TERHADAP PENCEMARAN AIR SUNGAI OLEH LIMBAH RUMAH TANGGA DI INDONESIA - Gede Sukhwan Oka Winawan (Jurnal Komunikasi Hukum, 2025)
River water is included in the category of natural resources that have a function in supporting human survival and ecosystem sustainability. In addition to being the main provider of water for domestic needs, agriculture, fisheries sector, and industrial activities, rivers also play an important role as a supporter of the water system and regulator of environmental stability as a whole. The rapid increase in population, accompanied by the expansion of residential areas, has a significant impact on the volume of waste generated from household activities. Liquid waste from domestic activities, if not managed properly, has the potential to cause damage to the environment. This research is included in the type of descriptive research. The approach applied is normative juridical, which means that in examining the problems studied, researchers refer to legal norms contained in laws and regulations. Household waste is one of the main contributors to river water pollution in Indonesia. This waste includes liquid waste (such as used water from washing, bathing, and cooking), as well as solid waste such as organic and inorganic waste that is dumped directly into rivers without going through a processing process. The applicable regulations and policies serve as legal references as well as technical guidelines for the government and related agencies, including the Environmental Service at the district level, in carrying out the process of taking action against perpetrators of river pollution. The village government has a strategic role in supervising household activities that have the potential to pollute water bodies, and can impose sanctions on violations that occur.